Dampak Pembangunan Jalan Tol Probolinggo Banyuwangi (Probowangi) Terhadap Kondisi Sosial Ekonomi Petani di Desa Demung Kecamatan Besuki - Romzatul Widad; Zulfiyan Aldiansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Infrastructure development is one of the government's main strategies for promoting national economic growth, improving regional connectivity, and accelerating the distribution of goods and services. One form of infrastructure development that continues to be developed is toll roads. However, this development also has a significant impact on the community, especially vulnerable groups such as farmers. Demung village, located in Besuki sub-district, is one of the areas directly affected by the toll road construction project. Farmers are also a group of people who are highly dependent on land availability and environmental conditions, and are experiencing changes in social and economic aspects. The conversion of agricultural land into toll road construction areas, changes in production patterns, and shifts in social structure are issues that need attention...The impact is seen not only in accessibility, but also in the social and economic conditions of farmers. These changes include land relocation, patterns of social interaction. with the construction of the toll road, there are fifteen farmers affected, especially in demung village, besuki subdistrict. the problem faced is how the impact of probowangi toll road construction on the socio-economic conditions of farmers in demung village, besuki subdistrict. This study aims to determine the impact of toll road construction on the socio-economic conditions of farmers around the besuki toll road in demung village. The impact is not only seen in the accessibility, but also in the social and economic conditions of the farmers. With the construction of the toll road, there are fifteen farmers affected, especially in demung village, besuki sub-district. the problem faced is how the impact of probowangi toll road construction on the socio-economic conditions of farmers in demung village, besuki sub-district. This study aims to determine the impact of toll road construction on the socio-economic conditions of farmers around the Besuki Toll Road in Demung Village. This research method adopts a descriptive qualitative approach. The results showed that the change in the function of agricultural land into a toll road had both negative and positive impacts. The positive impact of this research is that the value of land increases, the farmers' land that is put on the toll road body experiences a very high price increase; the negative impact is the loss of agricultural land, and also many farmers lose their social identity.